Southern and Eastern Africa - Agricultural trade policy debates and deveopments: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
Food and agricultural sector policy is a politically charged issue throughout Southern and Eastern Africa. Food security concerns, the growing focus on expanding national food production, and aspirations to develop value-added food processing industries pose important policy challenges in terms of balancing the interests of consumers, agricultural producers and food processors. Despite the existence of a number of regional integration initiatives (two customs unions, two free trade areas, and a grand free trade area under negotiation), several obstacles to intra-regional trade of food and agricultural products exist, in the form of exceptions to the principle of the free movement of goods and to the common external tariff, divergent policies on food safety requirements, sanitary and phytosanitary (SPS) measures, and divergent product standards. There are also other non-policy-based barriers to trade (poor roads, administrative procedures, logistical constraints, corruption, etc.). This Executive Brief focuses on 2012-13 developments in the Southern and Eastern African agricultural sector. After analyzing the main developments in the regional integration processes and the use of agricultural trade policy tools, it highlights the main policy debates and issues on the agenda.